Microbial biomass and N mineralization in mixed plantations of broadleaves and nitrogen-fixing species - Pereira, Ermelinda (2012)
The present study was conducted in a 10-year-old trial of mixed plantation located in the Northeast of Portugal. This study was developed in the three following treatments: pure of Robinia pseudoacacia; pure of Prunus avium and mixed of Prunus avium × Robinia pseudoacacia. To better understand the benefit of the consociation of an N-fixing species (Robinia pseudoacacia) with broadleaves quality timber production (Prunus avium), we compared the soil microbial biomass carbon and nitrogen, soil respiration and N-mineralization of these three situations. Net mineralization or immobilization of N in field soils is calculated from measured changes in the mineral-N content of largely undisturbed soil isolated inside tubes in situ. Soil microbial biomass carbon (SMB-C) and nitrogen (SMB-N) were determined by fumigation-extraction method. We also determined the ratio of SMB-C to soil organic carbon (Cmic/Corg) as an indicator of soil organic matter quality or availability, and the metabolic quotient (qCO2) as a measure of microbial efficiency. Microorganisms are generally considered as the driving force or catalyst behind the decomposition process. In this sense, the magnitude Microbial biomass C (MBC) may indicate potential rate of C flux. Indeed, MBC is commonly described as a living or active pool in models that simulate organic C turnover in soils, and the size of this pool directly affects the model outputs. Soil enzymes are mostly of microbial origin and are closely related to microbial biomass. Desidrogenase is one of the most frequently used enzyme tests for the measurement of total microbial activity in soil. This was the methodology used in this study.